Avaliação da integridade intestinal vinculada ao perfil comportamental de Drosophila melanogaster expostas ao Bisfenol A - (:unkn) unknown (Universidade Federal do Pampa, 2023)
We have an efficient intestinal microbiota, which has several roles, such as the absorption of nutrients, bringing benefits to our body. For years, the importance of the intestinal microbiota has been studied, as well as the relationship between its imbalance and the emergence of diseases, making the intestine the object of study by many scientists. Studies show that toxic substances, such as Bisphenol A (BPA), can be relevant to our health when released by plastic materials in direct contact with heat or cooling. The present work aimed to analyze the integrity of the mid-intestinal tissue of Drosophila melanogaster larvae when exposed to BPA at concentrations of 0.1, 1 and 10 mM. To carry out the analysis, 2nd stage larvae were exposed to BPA in petri dishes for 48 hours, subsequent analyzes were carried out. Exposure to BPA caused damage to intestinal integrity in Drosophila melanogaster larvae and changes in locomotor behavior, where the larva exposed to the highest concentration traveled fewer quadrants compared to the control, demonstrating negative effects caused by BPA. Due to the action of this chemical compound in the body, its use in the manufacture of some materials becomes a concern, as the use of BPA in different concentrations can cause damage to intestinal cells, which may be associated with behavioral changes.
Assessment of intestinal integrity linked to the behavioral profile of Drosophila melanogaster exposed to Bisphenol A
Keywords: Bisfenol A; Intestino médio; Integridade intestinal; Bisphenol A; Midgut; Intestinal integrity; CNPQ::CIENCIAS EXATAS E DA TERRA